A METHOD OF COMPARATIVE EVALUATION OF CONTROL SYSTEMS BY THE SET OF PERFORMANCE MEASURES - Drevetskyi, Volodymyr; Kovela, Ivan; Kutia, Vitalii (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2017)
It was proposed a method of comparative estimation of process control loops based on a complex of direct and indirect performance measurers taking into account stability margins. It was presented a comparison algorithm for complex performance parameter considering the influence of stability margins of a control loop on its properties. Features of the method of comparative estimation of process control systems performance have been considered as an example for the closed loop feedback control system with PI controller (4 variations) and the second order plus transport delay plant.